Considering the Use of Hot Potatoes in Reading Comprehension, Autonomy in TEFL, and Learning Styles - Zúñiga Vargas, Juan Pablo (2014)
This article describes the possibility of using the authoring tool called “Hot Potatoes” as a valuable resource in the design of customized exercises and didactic units for reading comprehension courses. In so doing, the authors will also consider the construct of autonomy in the Teaching English as a Foreign Language (TEFL). Specifically, the authors will refer to learner autonomy as a desirable characteristic in students in the formative process of developing their reading skills. In addition, teacher autonomy, a frequently forgotten facet of autonomy, will be discussed. Learning styles and their connection with reading comprehension will also be considered. Finally, the authors will describe some generalities about the teaching of reading, the basic features of “Hot Potatoes,” and some practical ideas about how to use this software in reading comprehension courses.